HOMICIDE BY MULTIPLE PERSONALITY DISORDER IN SIDNEY SHELDON’S TELL ME YOUR DREAMS: A PSYCHOLOGICAL APPROACH - Seffi Rahmawati (Universitas PGRI Madiun, 2015)
Multiple Personality Disorder can be seen in novel entitled Tell Me Your Dreams. The character, Ashley Patterson was committed the homicide to five men. This analysis will focus on (1) the symptoms of Multiple Personality Disorder and, (2) the affect of Multiple Personality Disorder to the homicide. The research will use the qualitative research and documentation. The source of data is from Sheldon’s novel Tell Me Your Dreams as the primary data. The supporting are from journal, book, article, etc relating to psychology. This research will use psychological approach. The theory that use to analyze are the Multiple Personality Disorder, homicide, and psychology of literature by Wellek and Warren. The result of the research reveals that (a) the character of Ashley get the psychological oppression from the abuse and neglect in young age. It makes her build the defense from the trigger of re-experience in the present life. (b) the defenses lead the character of Ashley take the impulsive action and the worst was killed people.